Vulnerability, the other side of economic liberalization - Diaz, Vivianne Ventura (1999)
Analyzes the trade channels through which the East Asian financial crisis spread. Points out that the 1997-1998 crisis, with but a few exceptions, affected soley developing economies and the most advanced and successful ones at that, those that had distinguished themselves for having implementted policies aimed at improving their insertion in the world economy.